Electrospun Bioactive Wound Dressing Containing Colloidal Dispersions of Birch Bark Dry Extract - Francis Kamau Mwiiri; Johanna M. Brandner; Rolf Daniels (Pharmaceutics, 2020)
Novel birch bark dry extract (TE)-loaded polyvinyl alcohol (PVA) fiber mats intended for wound therapy were developed through an electrospinning process. Colloidal dispersions containing TE as the active substance were prepared by the high-pressure homogenization (HPH) technique using hydrogenated phospholipids as stabilizer. Subsequently, the colloidal dispersions were blended with aqueous PVA solutions in the ratio of 60:40 (wt.%) and electrospun to form the nanofiber mats. Fiber morphology examined using scanning electron microscopy (SEM) indicated that fibers were uniform and achieved diameters in the size range of 300–1586 nm. Confocal Raman spectral imaging gave good evidence that triterpenes were encapsulated within the electrospun mats. In vitro drug release and ex vivo permeation studies indicated that the electrospun nanofibers showed a sustained release of betulin, the main component of birch bark dry extract, making the examined dressings highly applicable for several wound care applications. Ex vivo wound healing studies proved that electrospun fiber mats containing TE accelerated wound healing significantly more than TE oleogel, which was comparable to an authorized product that consists of TE and sunflower oil and has proved to enhance wound healing. Therefore, our results conclude that the developed TE-PVA-based dressings show promising potential for wound therapy, an area where effective remedy is needed.